Management Control Systems in the Internet-enabled Business Models : A Case-study on control dynamics: unravelling the interplay within an open-source business model and its ecosystem - Saarinen, Anne (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
This study builds on two concepts: management control (MC) and Internet-enabled business model (IEBM).MC is a wide set of formal or informal mechanisms that the management has implemented for aligning people’s behaviour towards the set organisational goals and answering to control needs that arise from the business environment. In this study, the focus is on a business model context-driven set of controls. Unlike in the discussion of MC as a system is typical, I use the word system to describe such management control that is implemented by the company management for aligning employees’ behaviour towards the strategic targets. In the IEBM, the Internet is crucial infrastructure and enabler for existence. The choice of technology made by company management divides IEBMs into utilisers of paid and free technology. Value creation and capture can only realise by acting as part of an ecosystem of the same technology users. Technology, the ecosystem, value creation mechanisms, and innovation are the central attributes that describe IEBMs. Those significantly affect the design of MCS as well. However, whilst the MCS literature has concentrated on strategic features of innovation and development, the IEBM level of decisions and the MCS package designed because of them, has not yet been explored much in the MCS literature. The case company of this interpretive study is a free technology software developer for system coders globally. This study contributes to our existing knowledge by showing that the MCS package design is two-fold: MCS for the behavioural control within the organisation, and MCS for the external actors in the ecosystem. Further, the MCS package for the organisation is designed around three main control questions: ensuring value creation and capture, diminishing risks, and enabling of innovation. In addition, the package has another layer, where IEBM control systems aim in the direction of external actors, the ecosystem. That layer builds on a strong organisational culture, some very labelling activity, an anchor/core practice, and also on such social, technical, economic, and institutional minimal structures, which provide governance but allow considerable independence at the same. Those structures govern the ecosystem and the IEBM reciprocally.

Tässä tutkimuksessa tarkastelen yrityksen ohjausjärjestelmiä (management control, MC) Internet-pohjaisen liiketoimintamallin (Internet-enabled business model, IEBM) johtamisessa. Ohjausjärjestelmät ovat virallisia tai epävirallisia käytänteitä, jotka yritysjohto on käyttöönottanut. Niiden tarkoituksena on edistää määriteltyjen tavoitteiden saavuttamista ohjaamalla ja yhtenäistämällä työntekijöiden käyttäytymistä organisaatiossa. Tässä tutkimuksessa käsittelen ohjausjärjestelmiä ensisijaisesti Internet-liiketoimintamallin näkökulmasta. Käytän sanaa järjestelmä (system) kuvaamaan sellaista ohjausta, joka on yrityksen johdon toteuttamaa, ohjaa työntekijöiden käyttäytymistä, ja joka ohjaa kohti organisaation strategisia tavoitteita. Internet-pohjaisella liiketoimintamallilla tarkoitan liiketoimintamallia, jossa Internet on elinehto. Yritysjohto voi valita maksullisen tai maksuttoman teknologian käytön liiketoimintamalliinsa. Teknologia on avainasemassa, ja arvonluonti onnistuu vain toimimalla osana samaa teknologiaa käyttävien toimijoiden ekosysteemiä. Teknologia ja sen mukanaan tuoma ekosysteemi, arvonluonnin mekanismit, sekä innovatiivisten tuotteiden ja palveluiden kehittäminen ovat IEBM’ien keskeisimpiä piirteitä. Nämä vaikuttavat oleellisesti ohjausjärjestelmien kokonaispakettiin (MCS package), mutta tätä yhteyttä ei ole MC-kirjallisuudessa juurikaan tutkittu. Tämän tulkitsevan tutkimuksen tapausyritys käyttää maksutonta teknologiaa kehittäessään ohjelmistotuotteita maailman järjestelmäkoodareille. Tutkimus osoittaa, että ohjausjärjestelmien paketissa on kahden tasoisia järjestelmiä, käyttäytymistä organisaation sisällä ohjaavia sekä ekosysteemin ohjausta tavoittelevia. Organisaation sisäistä käyttäytymistä ohjaavat järjestelmät keskittyvät kolmeen ohjaustarpeeseen: arvonluontiin, riskien pienentämiseen ja innovaatioiden mahdollistamiseen. Ekosysteemin toimijoihin, eli yrityksen rajojen ulkopuolelle, suuntautuva ohjaus rakentuu vahvalle organisaatiokulttuurille. Lisäksi ankkuri-/ydinkäytäntö liittää organisaation koko toiminnan tiiviisti ympäristöönsä. Sosiaaliset, tekniset, taloudelliset ja institutionaaliset minimaaliset rakenteet, jotka toisaalta ohjaavat, mutta samalla sallivat laajan itsenäisen toiminnan, luovat vastavuoroisen ohjausjärjestelmän liiketoimintamallin ja ekosysteemin välille.